Implementation of Data Mining in the Application of K-Medoid Clustering Algorithm for the Distribution of New Students at Pondok Pesantren Mukhtariyah Ambai - Hamsiah, Hamsiah (The Future of Education Journal, 2025)
Pondok Pesantren Muhktariyah Ambai is a private Islamic boarding school that accommodates both Tsanawiyah (junior high) and Aliyah (senior high) levels. It is located in Ambai Bawah Village, Sitinjau Laut District, Kerinci Regency, Jambi Province. Each year, the school admits new students from various schools across Kerinci Regency, Sungai Penuh City, and other surrounding regions. This study applies data mining concepts using the K-Medoid clustering algorithm to determine the distribution of new students based on their geographic origins and previous schools before continuing their education at Pondok Pesantren Muhktariyah Ambai. The data obtained can help the foundation identify which schools contribute the highest number of new students. The dataset used in this study consists of 2024 student data with attributes including Name, Gender, Previous School, and Address. The results of the study show the formation of three clusters: Cluster 0 consists of the largest group of new students, primarily from the Ambai area and from elementary schools located in Ambai Village; Cluster 1 includes students from Sungai Penuh and its surroundings; and Cluster 2 represents students from outside the region, who make up the smallest number of new enrollees at Pondok Pesantren Muhktariyah Ambai.